Carbon emissions and the economic costs of transport policy in Sweden - Glenn W. Harrison; Bengt Kriström (Fondazione Eni Enrico Mattei (FEEM), 1997)
In recent years the Swedish transport system has become a target for intensive political discussion. One can single out "the environment" and "infrastructure" as the typical buzzwords of this debate. Sweden has invested a significant amount of its prestige in showing that it can stick to agreements made in conjunction with the Rio Summit in 1992. The growing transport sector is a key challenge, and perhaps it is here that Sweden will face the most substantial difficulties in meeting the obligations. Nevertheless, the notion that it is possible to create an environmentally "friendly" transport sector has become a theme of many recent proposals on the future of Swedish transport policy. We evaluate several of these proposals by constructing and simulating a computable general equilibrium (CGE) model of Sweden. We review the salient features of the transport policy debate in Sweden in section 1. The model is described in section 2, and the main results presented in section 3.
Keywords: 330